When Moving Up Implies Moving Out: Rural Adolescent Conflict in the Transition to Adulthood - Joel M. Hektner (Journal of Research in Rural Education, 1995)
What is the influence of community context on the attitudes and plans ofrural and nonrural adolescents regarding their future geographic and social mobility? Because of the limited range of careers available in rural areas, rural adolescents may be more likely than their nonrural counterparts to aspire to careers that require their moving away from the people and places to which they are strongly attached. The incompatibility of career aspirations with future residential preferences may result in conflict. To test these hypotheses, I used questionnaire datafrom 918 Sth, l Oth, and 12th graders from three midwestern school districts participating in the Sloan Study of Youth and Social Development. Analysis reveals a greater prevalence among rural than among nonrural adolescents ofa potential conflict between the perceived importance of staying close to parents and relatives and moving away from their area. Tenth graders expressing this potential conflict are more likely to have lower educational aspirations and to plan to delay college entry. Conflicted rural youth also indicate feeling more empty and angry about their futures. Rural males appear to be most likely to experience the conflict and the negative outcomes associated with it.